Factors Affecting Students’ Entrepreneurial Motivation during COVID-19 Pandemic - Farica Ayu Nabila; Icha Putri Kusuma; Shavira Ika Putri; Aftina Nurul Husna (Urecol Journal. Part G: Multidisciplinary Research, 2022)
Motivation is an encouragement or enthusiasm to move forward. Entrepreneurial motivation in students is the encouragement or effort of students to make creative, innovative, and useful efforts by developing ideas and resources to find opportunities and improve life, and engage in business competition. At this time technological developments cause changes in culture and people's daily lives, especially during this Covid-19 pandemic where all activities are carried out indoors. Many entrepreneurs who are heavily affected by the Covid-19 pandemic are none other than students who are also entrepreneurs. This study aims to determine the factors that influence the entrepreneurial motivation of students during the pandemic and the things that cause them to persist and not give up. By method. The research design used is a qualitative case study. With the subject of 3 students who are entrepreneurs. The data collection technique was carried out by direct interviews in the Campus 1 environment of the Muhammadiyah University of Magelang. The sampling technique used in this research is purposive sampling. The results of this study show that the impact of the pandemic on entrepreneurship is very large. Starting from the lack of customers to declining income, but there are several factors that arise in students to remain entrepreneurship, including economic factors that must be fulfilled as well as hobbies and good business prospects for the future.